PERCEPTION OF FINAL YEAR BPT STUDENTS OF GUJARAT REGARDING ADULT SPINAL DEFORMITY. - Dr. Ridhi J. Vora; Dr. Palak J. Vora (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background:  Adult spinal deformity (ASD) can significantly impact an individual's quality of life, leading to pain, functional impairment, and in severe cases, neurological complications. The complex nature of adult spinal deformities requires a multidisciplinary approach to diagnosis and management, involving orthopedic surgeons, neurosurgeons, pain specialists, and physical therapists.Methodology: In this study, Google form was sent to 54 physiotherapy institutes in Gujarat with 2418 final year students. We received 345 responses, surpassing the required sample size of 332.6 (95% C.I.). The form covered demographics and questions on ASD, ensuring participant confidentiality for ethical reasons.Results: The results revealed that, 79% acknowledge poor ergonomics impact on spinal deformity. 92% recognize educating patients on proper posture for ASD is crucial. 47% support radiological investigations for back pain. 72% believe in the effectiveness of bracing, despite no literature proof. Regarding surgical correction, 28% deny reoccurrence, 35% are unsure, and 42% believe physiotherapy alone can manage spinal deformity, while 27% disagree.Conclusion: Enhancing patient well-being in terms of preventing deformity or disability related to ASD requires measures focused on prevention and outcomes. The prevention of complications arising from spinal deformities is attainable by timely modification of causative factors. Achieving this goal relies on the proper alignment of physiotherapists' perceptions in the right direction.      Abbreviations: BPT: Bachelor of PhysiotherapyASD: Adult spinal deformityPT: Physiotherapy